Research goals for minimizing the cost of CO2 capture when using steam methane reforming for hydrogen production - Hari Mantripragada; Rafael De Leon; Alexander Zoelle; Mark Woods; Eric Lewis; Timothy Fout; Travis Shultz; Eric Grol; Sally Homsy (Carbon Capture Science & Technology)
This paper presents a techno-economic assessment of adding state-of-the-art solvent-based CO2 capture technologies to greenfield steam methane reforming (SMR)-based H2 production plants and quantifies the impacts of improvements in CO2 capture technology. Current conventional capture technologies are reviewed, and future technologies in intermediate and long-term scenarios are analyzed. The results show that SMR plants fitted with high efficiency solvent-based capture technologies consume the same amount of natural gas as a conventional SMR plant without capture, despite capturing most of the CO2 and producing the same amount of H2. Overall, improvements in reboiler duty and reductions in capital costs can significantly reduce the cost of H2 production and cost of capture. Particularly, the reboiler duty of pre-combustion capture and the capital cost of post-combustion capture have the greatest impact. Based on the results, research goals are suggested. Solvent development is recommended—particularly pre-combustion solvents—for reducing the reboiler duties, and process schemes to reduce the capital costs. Costlier but more efficient solvents can be considered. A sensitivity analysis using natural gas price shows that technological improvements can reduce the impacts of high natural gas prices. The degree of economic feasibility of CO2 capture increases with improvements to the capture technology.